Giant superficial angiomyxoma of the male perineum: A case report - Yan, Sheng; Zou, Yuhua; Liao, Xinzhi; Zhong, Cunzhi; Liu, Shengyin; Huang, Sigen; Zou, Junrong; Liu, Quanliang (Frontiers in Surgery, 2023)
Superficial angiomyxoma (SA) is a rare benign tumor that occurs either in the superficial dermis or subcutaneously. It often occurs in the trunk, neck, or limbs, and grows slowly. The diameter of the tumor is usually less than 5 cm. A giant SA of the perineum in men is very rare. We detailed the diagnosis and treatment of male patients with perineal SA and performed a literature review. We report a case of a 42-year-old male patient. He was admitted to hospital with a perineal mass found more than 1 year previously. A pelvic contrast-enhanced computed tomography scan in our hospital suggests that a round slightly hypointense foci of about 6.0 cm × 8.6 cm × 4.5 cm in size with still clear borders was seen below the penile corpus cavernosum in the perineum. We performed a perineal mass excision under continuous epidural anesthesia. A postoperative pathology report diagnosed perineal SA. There was no recurrence at follow-up for 27 months up to May 2022. Perineal SA is rare and should be combined with patient history and imaging to ensure complete excision of the mass margins. Adherence to long-term postoperative follow-up is the key to curing this case.